Panax notoginseng Saponins Promote Cell Death and Chemosensitivity in Pancreatic Cancer through the Apoptosis and Autophagy Pathways - Yao, Li-Chao; Wu, Lun; Wang, Wei; Zhai, Lu-Lu; Ye, Lin; Xiang, Feng; Tang, Zhi-Gang (Anti-cancer agents in medicinal chemistry, 2021)
Panax notoginseng Saponins (PNS) is used as a traditional Chinese medicine for ischemic stroke and cardiovascular disease; it has been proven to possess anticancer activity recently. In this study, we aimed to explore the curative anticancer effect and potential mechanisms of PNS in pancreatic cancer cells. Pancreatic cancer Miapaca2 and PANC-1 cells were treated with PNS and Gemcitabine (Gem), respectively. Then the cell viability was assessed by CCK-8 assay, cell proliferation was tested by colony formation assay and EdU cell proliferation assay, cell migration and invasiveness were tested by wound healing assay and transwell assay, respectively, and cell apoptosis was detected by flow cytometry. Finally, we detected the expression levels of proteins related to migration, apoptosis and autophagy through Western blotting. PNS not only inhibited the proliferation, migration, invasion and autophagy of Miapaca2 and PANC-1 cells, but also induced apoptosis and promoted chemosensitivity of pancreatic cancer cells to Gem. PNS may exhibit cytotoxicity and increase chemosensitivity of pancreatic cancer cells to Gem by inhibiting autophagy and inducing apoptosis, providing a new strategy and potential treatment option for pancreatic cancer.